Literatura i sztuka w nauczaniu języka polskiego jako obcego (propozycje metodyczne) - Hejda, Danuta (Dydaktyka Polonistyczna, 2015)
The author draws the attention to the role of information in the field of literature and art in the process of teaching Polish as a foreign language. The two fields are treated as important components of knowledge about Poland and the elements which create sociocultural competences. The advised methods and teaching techniques useful in the following fields are suggested.